Gerenciamento terminológico empresarial em libras: o caso da venda de gelato Il Sordo - Santos, Almir Barbosa dos (2025)
Corporate Terminology Management (CTM) is a specialized area of language that conveys terms (Cabré, 1999; Temmerman, 2000) related to management and standardization, aiming to ensure effective communication both within the community of practice and with the broader public (Eckert, 2012). In the business sector, this type of terminology seeks to transmit specialized language that enhances communication as a driving force, minimizing potential disruptions in the transmission of essential information—particularly in the management of expansionist and entrepreneurial possibilities (Müller, 2013; Batista, 2011). The focus of this dissertation was the terminological organization of products sold by il Sordo, a business distinguished by its use of Brazilian Sign Language (Libras) as a central element of its identity and operations. The study was based on the premise that the specific terms used in il Sordo’s sales chain can be cataloged and managed through terminological records, contributing to the standardization of corporate communication and reinforcing Libras as an inclusive element. The research was guided by two central questions: How can the terminological constructions of products sold at il Sordo be organized? In what ways does Libras consolidate itself as an essential identity marker of the company? The central hypothesis of this study is that the deaf attendants at il Sordo use standardized sign terms to represent products, as a result of their participation in a consolidated community of practice and the fact that they all originate from the same state, Sergipe. Therefore, the terminological formalization of Libras at il Sordo emerged as a key factor in its expansion and standardization. The general objective of the study was to organize the corporate terminology of il Sordo, promoting a terminological management system that supports the inclusion of Libras in the business context. Specific objectives included cataloging product-related terminologies, developing terminological records to systematize the sign terms, and designing a model that could eventually lead to the creation of a terminological manual for future franchise operations. The research adopted a qualitative-quantitative approach, using semi-structured interviews with il Sordo employees to understand the use of Libras in the company’s daily operations. In addition to data collection, a terminological analysis of the signs used in the commercial environment was conducted. The theoretical framework was based on three main approaches: the Communicative Theory of Terminology (Cabré, 1999), the Sociocognitive Theory of Terminology (Temmerman, 2000), and the concept of Community of Practice (Wenger, 1998; Eckert, 2004; 2012). The corpus of this study consists of 12 sign terms used at il Sordo, all related to ice cream flavors and types. The results show that the terminological organization, systematized through terminological records, plays a fundamental role in standardizing communication among deaf attendants, promoting greater clarity and consistency in the execution of signs. The analysis revealed that 50% of the terms were performed uniformly, indicating the consolidation of a shared linguistic repertoire among staff and enhancing communicative effectiveness in the professional setting. Furthermore, the inclusion of Libras as a foundational element of the company’s identity strengthens its brand and expands its potential for growth. The development of terminological records not only provided a practical tool for employees but also established a model for future terminological management initiatives in businesses that operate with Libras. The study also confirmed that the use of Libras extends beyond internal communication, becoming both a competitive advantage and a core component of il Sordo’s organizational identity.